Breakthrough supply chains : how companies and nations can thrive and prosper in an uncertain world - Gopal, Christopher; Tyndall, Gene; Partsch, Wolfgang; Iakovou, Eleftherios (McGraw Hill-Ascent Audio, 2023)
A timely guide to rethinking and reinventing supply chains with breakthrough thinking to benefits your organization, the economy, and the world As global business and geopolitical conditions have changed radically, it is imperative that supply chain strategies and operations transform to thrive in a volatile environment. Leaders at corporations, public agencies, national security, and public health recognize the importance of resilience, agility and flexibility. Breakthrough Supply Chains provides a comprehensive view of end-to-end supply chains and dispels the common myths about them. It provides "breakthrough thinking" principles that address critical topics for enterprise and public policy: how supply chains have enabled profitable and beneficial growth in the evolving world; the evolution of "the new customers" and what they demand; the critical success factors for managing demand and supply in a complex and risky world; information, data, governance, analytics and measurements that guide strategic choices; resilience, risk, and supply assurance; and sustainability and the environment. Whether you are an organizational manager, government agency leader, or member of the interested public, Breakthrough Supply Chains reinvents the supply chain with far-reaching effects. This is your go-to guide